Hubungan Mutu Pelayanan Petugas Kesehatan Terhadap Minat Kunjungan Ulang Pasien Rawat Jalan di Puskesmas X - Hairil Akbar; Heriyana Amir; Suci Rahayu Ningsih; Widya Astuti (Universitas Pekalongan, 2020)
The number of outpatient visits in the Xcommunity health center in 2016 was 32633 patients, and in 2017 the number of visits increased by 38374 patients, while in 2018 the number of visits decreased by 36604 patients. Based on data from outpatient visits at X health center that the number of patient visits decreased, where in 2017 increased and in 2018 decreased the number of patient visits.The purpose of the study was to determine the relationship between the quality of health care services and the interest of outpatient visits to the X community health center.The type of research conducted was observational analytic research using a cross sectional study approach. This research was carried out in the technical service unit of the X community health center in 2019. The population was all patients using outpatient care facilities at Cipancuh Health Center in 2019, with 36604 outpatients. The sample size is 100 people. Sampling is done by simple random sampling.Statistical test results, namely the quality of health services ( value = 0,000) are related to the interest of outpatient visits in the Technical Implementation Unit of the X community Health Center in 2019.It is expected that the staff will further improve the quality of their services in the hope that patients who use outpatient facilities. Keywords : Quality of health service,Interest in repeat visits